EFISIENSI PEMASARAN GABAH DAN KEUNTUNGAN USAHATANI PADI (Oryza sativa) ANGGOTA GABUNGAN KELOMPOK TANI - Adi Ismanto; erwin erfianingsih (Universitas Bondowoso, 2021)
Aimed of this study was to determine whether the efficient marketing of grain being sold to rice milling company, whether by purchase price of paddy rice milling companies are not detrimental to farmers and farms owned by farmers who sell grain to the mill, rice farmers profitable or not. Data used are primary data collected directly from the respondent farmers through direct interview method and secondary data obtained from several goverment institutions and related research intitutions. Sample taken 30 farmer respondents who participated planting cropping system simultaneously legowo using simple random sampling method. The results showed that the marketing of grain by farmers to rice milling company is not efficient, the purchase price of grain by rice mills company is not detrimental to farmers, paddy farming owned by farmers who sell grain to the mills company are profitable.